(untitled) (Zoological Records and Reviews, 2025)
Modern zoology has undergone a profound disciplinary transformation: questions that were once the exclusive domain of natural history and field biology now draw equally on molecular genetics, computational data science, physics-inspired modelling, social science, economics, and engineering. This interdisciplinary convergence is not merely methodological – it reflects a conceptual reorientation in which the boundaries between zoology and neighbouring disciplines have become permeable, generating hybrid research fields (landscape genomics, conservation social science, movement biophysics, zoonotic epidemiology, animal-inspired robotics) whose most impactful outputs emerge precisely from the disciplinary interfaces. This review synthesises evidence from 182 primary studies (2010-2025) examining the structure, productivity, and conservation impact of interdisciplinary zoological research, evaluating seven major disciplinary integration domains: zoology-genomics, zoology-data science and AI, zoology-physics and engineering, zoology-social science, zoology-medicine (One Health), zoology-economics (natural capital), and zoology-earth observation. Bibliometric analysis of 14,240 interdisciplinary zoological publications (2015-2024) finds that papers crossing two or more disciplinary boundaries receive mean 2.4-fold higher citations than single-discipline zoological studies, produce 3.2-fold more policy documents, and attract 1.8-fold more media coverage. However, interdisciplinary research faces structural barriers – incompatible publication cultures, disciplinary funding silos, career incentive misalignments, and methodological translation challenges – that systematically undermine its production relative to its impact. A framework for designing, funding, and evaluating interdisciplinary zoological research programmes aligned with EU Horizon Europe partnership requirements is presented.